The Relation between Family Socioeconomic Status and Academic Performance in Chinese Adolescents - Yu, Minfei (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, due to high economic development, China has transformed from a society with relative equality in education to one with high inequality in education. How does the massive gap in socioeconomic status affect adolescents’ academic achievement? This study examined the moder-ating role of family socioeconomic status between the family atmosphere (i.e., parental involvement) and family investment (educational investment and tutoring funds) on junior high school academic achievement with 10,279 Chinese junior high school students (aged 12-16). The data came from the 2014-2015 China Education Panel Survey (CEPS), a large-scale nationally representative track-ing survey designed and implemented by the China Survey and Data Centre of Renmin University of China. The results of this study indicate that 1. socioeconomic status (The results of this study show that 1) socioeconomic status (parents’ education level) positively moderates the relationship be-tween academic achievement, family atmosphere (parental involvement), and adolescents’ academic performance. 2) socioeconomic status (parents’ income level) positively moderates the relationship between academic achievement, family investment, and adolescents’ academic performance. 3) so-cioeconomic status (parents’ income level) positively moderates the relationship between family in-vestment and adolescents’ academic performance. Thus, we can see that parental involvement and increased investment in education benefit junior high school students from families with high socioeco-nomic status. In contrast, junior high school students from low socioeconomic status do not enjoy this benefit. In the future, the government and society can develop family-based interventions to promote parental involvement and investment in education in low-SES families, which will, in turn, promote the educational attainment of adolescents. The results of this study have important implications for the development of family education in China.